Book Reviews. (June 2017) - Schipani, Andrés; Olmeda, Juan C.; Weeks, Gregory; Fernandes, Sujatha; Himley, Matthew; Moraes, Juan Andrés; de Arimatéia da Cruz, José; González‐Vicente, Rubén
ABSTRACT: Matthew Amengual, Politicized Enforcement in Argentina: Labor and Environmental Regulation . New York: Cambridge University Press, 2016. Figures, tables, appendix, notes, bibliography, index, 286 pp.; hardcover 99.99, ebook 80. Matthew C. Ingram, Crafting Courts in New Democracies: The Politics of Subnational Judicial Reform in Brazil and Mexico . Cambridge: Cambridge University Press, 2015. Maps, figures, tables, appendixes, bibliography, index, 392 pp.; hardcover, 110. Russell Crandall, The Salvador Option: The United States in El Salvador, 1977–1992 . New York: Cambridge University Press, 2016. Photographs, maps, figures, list of organizations, bibliography, index, 698 pp; hardcover 99.99, paperback 39.99, ebook 32. Luis Fernando Angosto‐Ferrández, Venezuela Reframed: Bolivarianism, Indigenous Peoples and Socialisms of the Twenty‐First Century . London: Zed Books, 2015. Appendix, bibliography, index, 312 pp.; paperback, ebook. Fábio de Castro, Barbara Hogenboom, and Michiel Baud, eds., Environmental Governance in Latin America . New York: Palgrave Macmillan, 2016. Tables, figures, map, bibliography, index, 350 pp.; hardcover 31, ebook. Eduardo Alemán and George Tsebelis, eds., Legislative Institutions and Lawmaking in Latin America . New York: Oxford University Press, 2016. Figures, tables, notes, bibliography, index, 296 pp.; hardcover 90, ebook. Joseph S. Tulchin, Latin America in International Politics: Challenging U.S. Hegemony . Boulder: Lynne Rienner, 2016. Bibliography, index, 235 pp.; hardcover 60. Kevin P. Gallagher, The China Triangle: Latin America's China Boom and the Fate of the Washington Consensus . New York: Oxford University Press, 2016. Tables, figures, bibliography, index, 256 pp.; hardcover 27.95, ebook.